Improving Self-Concept through Effective Interpersonal Communication - Fauzan Habibi; Nurfarhanah; Netrawati; Dina Sukma (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This research is influenced by a phenomenon that has occurred at State of Junior High School 27 Padang, namely low student interpersonal communication. Self-concept is one of the factors that influence students' interpersonal communication. This study aims to analyse the relationship between self-concept and interpersonal communication, the research method used is quantitative. This type of research is descriptive correlative. The population in this study was 364 student and the sample of this study was 190 student. The research instrument was a questionnaire raised with Likert scale measurement, the data analysed with descriptive correlation statistics with the help of SPSS version 25.00. The results show that students' self-concept is in the high category, which means that students already have a good self-image of themselves. Interpersonal communication is in the high category, indicating that students already have the ability to communicate effectively with others. There is a positive and significant increase between students' self-concept and interpersonal communication. This means that high and low interpersonal communication can be explained from self-concept, then interpersonal communication will be higher. The results of research data analysis obtained R = 0.213 with the degree of p = 0.003 (p < 0.005), R2 = 0.18.3%. This study proves that there is a positive and significant increase in self-concept and interpersonal communication of junior high school student. Keywords: Self-Concept, Interpersonal Communication, Improving Self-Concept